Anti-Phishing Add-On For Mozilla Firefox - Soong, Yie Thin (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Advancement in computing technology increase the number of Internet usage. In recent years, phishing attacks have increased exponentially and it is targeting at every sector of society. It is a continual threat that keep growing and it has been identified as one of the top cyber-crimes that impact consumers and businesses all around the world. Phishing itself is known as the process to divulge credentials by masking themselves as a trustworthy or familiar entity. With social networking on the rise, people are sharing their personal information everywhere, and have no idea if a website is truly what it seems to be. As a successful phishing attack can have disastrous consequences for the victims leading to financial losses and identity theft, there is a need to identify the legitimacy of the websites. Anti-phishing Add-on for Mozilla Firefox is proposed to detect phishing website by using the URL features. Particularly, different components from URL are derived and they are used to compute metrics for each component. Then, the URL metadata will be combined with the achieved metrics to determine legitimacy of the websites. Heuristics approach that aims to analyze the URL at browser level is used and the anti-phishing add-on developed has an accuracy ratio of 76.5% which is highly above the average value. The add-on developed hits the objectives of the project and even though it has an acceptable accuracy ratio, there is still room for improvements of the heuristics approach used. One of the future works is to re-formulate the threshold value and examine the heuristics approa